IMPLEMENTASI PEMBIASAAN SHOLAT DHUHA SEBAGAI BENTUK KARAKTER RELIGIUS PESERTA DIDIK DI MIN 1 PULANG PISAU - Gusti Marifattullah Alianto; Muhammad Tri Ramdhani; Ahmad Syarif (Almarhalah: Jurnal Pendidikan Islam, 2025)
This study aims to determine how the Implementation of Dhuha Prayer Habituation as a Form of Religious Character of Students at MIN 1 Pulang Pisau. The type of research in this Journal is qualitative research, which emphasizes analysis on the inductive inference process. The approach used by the author is a descriptive approach, the situation described in this study is the Implementation of Dhuha Prayer Habituation as a Form of Students' Religious Character at MIN 1 Pulang Pisau. Data collection is done by conducting observations, interviews, documentation. Data analysis uses data reduction analysis, data agreement, and conclusion drawing. The results of this study show: (1) The implementation of the dhuha prayer habituation program at MIN 1 Pulang Pisau is carried out every Tuesday and Saturday. Dhuha prayers are performed in congregation with students in grades IV-VI. The accompanying teacher and the class teacher monitor, accompany and direct from the beginning of the implementation until the end of the implementation. (2) The impact of religious character formation of students in grades IV-VI on the habituation of dhuha prayers can be said to be quite good. This is indicated by positive behavioral changes. These changes can be seen: first students have good morals towards Allah SWT, towards the Koran and towards friends. Second, his religious nature has increased. Third, his personality towards a more positive direction. (3) supporting and inhibiting factors for the implementation of dhuha prayer habituation in moral development. (1) Supporting factors. The supporting factors are motivation from teachers and parents, awareness and enthusiasm of the students themselves and the existence of sufficient facilities and infrastructure. (2) Supporting and inhibiting factors for the implementation of habituation of dhuha prayer as a form of religious character of students at MIN 1 Pulang Pisau include constraints from teachers, and constraints from students.